Molecular dynamics simulation of CO2 dissolution-diffusion in multi-component crude oil - Kang, Yulong; Zhang, Lei; Luo, Juan; Guo, Yuchuan; Cheng, Shiying; Wu, Di; Li, Kaifen; Guo, Shiqiang (Frontiers in Environmental Science, 2023)
In order to study the dissolution-diffusion process and mechanism of CO2 in multi-component crude oil, a model of multi-component crude oil system with octane as the main component and 16 other alkanes as a compound was constructed by using molecular dynamics simulation method. We estimated the CO2 density distribution in crude oil model and the shift in crude oil model volume change. We then investigated the microscopic influence mechanism of CO2 dissolution-diffusion on the volume expansion of crude oil by simulating the action of CO2 dissolution-diffusion in the multi-component crude oil model. Based on the variation law of mean square displacement between crude oil molecules, the dissolution and diffusion coefficients of CO2 were predicted, and the influence of CO2 dissolution-diffusion on crude oil mobility was analyzed. It is found that temperature intensifies the molecular thermal motion and increases the voids between alkane molecules, which promotes the dissolution of CO2 and encourages CO2 molecules to transmit, making the crude oil expand and viscosity decrease, and improving the flow ability of crude oil; with the enhancement of given pressure, the potential energy difference between the inside and outside of the crude oil model becomes larger, and the voids between alkane molecules become larger, which is favorable to the dissolution of CO2. Nevertheless, the action of CO2 molecules' diffusing in the crude oil sample is significantly limited or even tends to zero, besides, the mobility of crude oil is affected due to the advance of external pressure. The mechanism of CO2 dissolution and diffusion in multi-component crude oil is revealed at the microscopic level, and provides theoretical guidance for the development of CO2 flooding.